Perancangan Sistem Informasi Pegawai Kontrak Pada Pemerintah Kota Jambi - Nugraha, Wahyu; Febrianto, Feri; Yani, Herti; Hassandi, Irfan (Jurnal Sains dan Teknologi (JSIT), 2025)
The rapid development of Information and Communication Technology (ICT) has significantly impacted various aspects of human life, including governance. The City of Jambi, with an area of 205.58 km², manages approximately 7,147 Civil Servants (ASN) and 3,543 Contract Employees across various agencies. Human resource services in the city are managed by the Regional Civil Service and Human Resource Development Agency of Jambi City. Despite having a human resource management system in place, the current data collection process is still done manually using Microsoft Excel, which hampers data processing efficiency, causes frequent data duplication, and complicates reporting. To address these issues, this study aims to design a web-based Contract Employee Information System, which is expected to improve data accuracy and facilitate the management of employee information, both for ASN and Non-ASN employees. This system is anticipated to enhance the efficiency of data collection, storage, and reporting, while also supporting faster and more accurate decision-making in Jambi City Government